Low-Dose Computed Tomography for the Optimization of Radiation Dose Exposure in Patients with Crohn’s Disease - Richard G. Kavanagh; John O’Grady; Brian W. Carey; Patrick D. McLaughlin; Siobhan B. O’Neill; Michael M. Maher; Owen J. O’Connor (Gastroenterology Research and Practice)
Magnetic resonance imaging (MRI) is the mainstay method for the radiological imaging of the small bowel in patients with inflammatory bowel disease without the use of ionizing radiation. There are circumstances where imaging using ionizing radiation is required, particularly in the acute setting. This usually takes the form of computed tomography (CT). There has been a significant increase in the utilization of computed tomography (CT) for patients with Crohn’s disease as patients are frequently diagnosed at a relatively young age and require repeated imaging. Between seven and eleven percent of patients with IBD are exposed to high cumulative effective radiation doses (CEDs) (>35–75 mSv), mostly patients with Crohn’s disease (Newnham E 2007, Levi Z 2009, Hou JK 2014, Estay C 2015). This is primarily due to the more widespread and repeated use of CT, which accounts for 77% of radiation dose exposure amongst patients with Crohn’s disease (Desmond et al., 2008). Reports of the projected cancer risks from the increasing CT use (Berrington et al., 2007) have led to increased patient awareness regarding the potential health risks from ionizing radiation (Coakley et al., 2011). Our responsibilities as physicians caring for these patients include education regarding radiation risk and, when an investigation that utilizes ionizing radiation is required, to keep radiation doses as low as reasonably achievable: the “ALARA” principle. Recent advances in CT technology have facilitated substantial radiation dose reductions in many clinical settings, and several studies have demonstrated significantly decreased radiation doses in Crohn’s disease patients while maintaining diagnostic image quality. However, there is a balance to be struck between reducing radiation exposure and maintaining satisfactory image quality; if radiation dose is reduced excessively, the resulting CT images can be of poor quality and may be nondiagnostic. In this paper, we summarize the available evidence related to imaging of Crohn’s disease, radiation exposure, and risk, and we report recent advances in low-dose CT technology that have particular relevance.